Twelve years of Arctic ozone loss observed by the Odin satellite - Sagi, Kazutoshi; Urban, Joachim; Eriksson, Patrick; Murtagh, Donal (2013)
In 2011, several groups reported dramatic ozone depletion over the arctic polar region approaching that of the Antarctic ozone hole. Odin, The Swedish-led satellite project in collaboration with Canada, France and Finland, was launched in February 2001 and continues to produce profiles of chemical species relevant to understanding the middle and upper atmosphere.This study concerns ozone loss over the northern pole utilizing the 12 years of ozone data from Odin/SMR.The unstable nature of the arctic vortex due to the propagation of planetary waves from troposphere makes quantifying chemical ozone loss in the arctic more difficult. The assimilation technique using a transport model is useful for separating the dynamical and chemical changes in the ozone amount as demonstrated earlier by Roseval et al (2007) . We have applied this method with a number of improvements to study the inter-annual variability during the entire Odin period.